Effect of dietary black soldier fly larvae (Hermetia illucens) and bioconversion product of cocoa pod husk on performance and hematological profile of sheep. Issue 6 (March 2021) - Rahman, R; Laconi, E B; Jayanegara, A; Astuti, D A
Abstract: Bioconversion of cocoa pod husk (CPH) is a biological processing technique using black soldier fly (BSF) larvae to improve the quality of the CPH while being able to produce added value in the form of BSF larvae as a protein source of animal feed. The aim of this study was to evaluate in vivo complete feeds containing BSF larvae and bioconversion product of CPH on performance and hematological profile of sheep. This study used a randomized complete block design (RCBD) with 5 treatments and 4 replications, so that total number of sheep used were 20 heads, conducted for 12 weeks period. The treatments were: R1 (complete feed, control without BSF and bioconverted CPH), R2 (5% BSF), R3 (20% bioconverted CPH), R4 (2.5% BSF + 10% bioconverted CPH), and R5 (5% BSF + 20% bioconverted CPH). The BSF and bioconverted CPH were used to replace soybean meal and coffee husk, respectively. Data were analyzed by analysis of variance and continued with a post-hoc Duncan's test. Results revealed that replacement of soybean meal with BSF larvae and replacement of coffee husk with bioconverted CPH in the complete feed did not significantly affect performance of sheep, i.e., live weight gain, feed consumption and feed conversion ratio). Furthermore, different dietary treatments showed similar response on hematological profile of sheep. It can be concluded that BSF larvae and bioconverted CPH may be used to replace soybean meal and coffee husk, respectively, without any adverse effects on performance and hematological profile of sheep.